Stretching the truth - Crowther, G. (2000)
About the question: "Is stretching good for athletes?" The first important point of view is "Does stretching lead to improved muscle performance?" A second equally important question to ask of stretching is, "Does it help prevent injuries?" Caveats and conclusions: Several caveats should be kept in mind: First, the importance of flexibility (and thus stretching) varies considerably from sport to sport; what may suffice for distance runners may not be adequate for gymnasts, for instance. Second, all athletic endeavors require a certain range of motion around one's joints, and athletes who can't comfortably achieve this range can certainly benefit from flexibility training. Third, certain athletes with specific problems (such as muscle imbalances, chronic tightness, or recent injury) are likely to benefit from stretching even if others do not. And fourth, stretching may yield long-term health benefits which are not apparent in the short-term time scale (weeks to months) of most exercise-related research. Despite these caveats, though, the fact remains that there is little experimental evidence that stretching benefits the average (or above-average) distance runner.